Enhanced Piezoelectric Properties of Tetragonal (Bi1/2K1/2)TiO3 Lead‐Free Ceramics by Substitution of Pure Bi‐Based Bi(Mg2/3Nb1/3)O3. Issue 1 (24th September 2014) - Pan, Zhao; Wang, Qi; Chen, Jun; Liu, Chuang; Fan, Longlong; Liu, Laijun; Fang, Liang; Xing, Xianran; Viehland, D.
<x xml:space="preserve">Abstract</x> Crystal structure, piezoelectric, and dielectric properties were investigated in the new lead‐free BKT‐based piezoelectric ceramics of (1−x)(Bi1/2K1/2)TiO3‐xBi(Mg2/3Nb1/3)O3. The morphotropic phase boundary (MPB) of the system between tetragonal and rhombohedral phases lies near the composition of x = 0.02. The optimal piezoelectric property of small‐signal d33 is much enhanced to be 96 pC/N (x = 0.01), which is higher than any other BKT‐based compositions. By the introduction of Bi(Mg2/3Nb1/3)O3, the ceramics exhibit a lower coercive field EC. In addition, a relaxor‐like behavior with a frequency‐dependent Curie temperature Tm is observed, and high Curie temperature Tm around 380°C is obtained in the investigated system. This study suggests that the piezoelectric properties of BKT can be significantly improved by the means of Bi(Mg2/3Nb1/3)O3 substitution.